Cyclin D1 is a strong prognostic factor for survival in pancreatic cancer: Analysis of CD G870A polymorphism, FISH and immunohistochemistry. Issue 3 (2nd December 2014) - Bachmann, Kai; Neumann, Anna; Hinsch, Andrea; Nentwich, Michael F.; El Gammal, Alexander T.; Vashist, Yogesh; Perez, Daniel; Bockhorn, Maximilian; Izbicki, Jakob R.; Mann, Oliver
<x xml:space="preserve">Abstract</x> Background and Objective Cyclin D1 is an important regulator protein for the G1‐S cell cycle phase transition. The aim of this trial was to evaluate the impact of the CCND1 polymorphism G870A and corresponding protein expression and CCND1 amplification on the survival of the patients. Methods 425 patients with ductal pancreatic adenocarcinoma who underwent resection were included after histopathological confirmation. DNA was analyzed for Cyclin D1 polymorphisms, immunhistochemical examination and fluorescence in situ hybridization analysis of the tumor were performed. Results Overall, the mean survival was 22.9 months (20.5–25.3). The survival in patients with Cyclin D1 G870A polymorphism Adenine/Adenine was 15.1 months (95% CI 11.3–18.9), 21.5 months (17.4–25.6) for Adenine/Guanine, and 29.4 months (95% CI 23.8–35.0) for Guanine/Guanine (P = 0.003). A shorter survival was associated with strong/moderate protein expression in immunohistochemistry (IHC) compared to weak/no expression (P = 0.028). Additionally, a significant coherency between unfavourable polymorphism (AA/AG) and increased protein expression was detected (P = 0.005). Conclusions A strong impact on survival of Cyclin D1 G870A polymorphism and the detected corresponding protein expression was found. The biological mechanism of CCND1 in carcinogenesis has not been fully examined; but at present Cyclin D1 seems to be an interesting biomarker for the prognosis of ductal adenocarcinoma. J. Surg. Oncol. 2015 111:316–323. © 2014 Wiley Periodicals, Inc.